PENGARUH E-WOM DAN ENDORSER TERHADAP PURCHASE INTENTION MELALUI BRAND IMAGE PADA PRODUK GADGET GAMING - Jamal Hasbi; Mohamad Rizan; Rahmi Rahmi (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The purpose of this study is to determine the effect of electronic word of mouth on brand image, the influence of endorsers on brand image, the influence of brand image on purchase intentions, the influence of e-WoM on purchase intentions, the influence of endorsers on intentions, the influence of e-WoM on purchase intentions through brand image, the influence of endorsers on purchase intention through brand image, on gaming gadgets. The data collection method used was a survey method with a questionnaire as an instrument. The collected research sample was 293 respondents who knew about gaming gadgets. Products in Jabodetabek aged 17 years and over, had seen endorser activity from gaming gadgets for the last six months. Software used in data analysis is SPSS and SEM (Structural Equation Model) from LISREL. The results of this study's hypothesis testing are all accepted hypotheses